(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Online social networks such as Facebook or Twitter contains user’s details, and some malicious users will hack social network database to steal or breach users’ information. Usually, all fake user’s main intention is to send friend request to normal users to hack their machine or to steal their data and never they will have many numbers of posts or have many following friends and their account age also will have a smaller number of years. By analysing this features Facebook will mark whether user profile is fake or genuine. Therefore, to protect the users’ data, this project uses artificial neural networks (ANNs) to identify whether given social network account details are from genuine or fake users. ANN algorithm will be trained with all previous users fake and genuine account dataset then this ANN pretrained model will be applied on new test data to identify whether the given new account details are from genuine or fake users.